Adolescent Back Pain and Associated Backpack Loading, Locker Use, and Online Textbook Alternatives - Angela MacCabe; Patti Berg-Poppe; Meredyth Arnott (Shiraz University of Medical Sciences, 2017)
Background: The incidence of childhood back pain is well established. The purpose of this study was to explore relationships between adolescent back pain and characteristics of load carrying, and behaviors such as locker and online textbook use. Methods:Data was collected from adolescents at three different schools. Students and their backpacks were weighed to determine backpack weight relative to body weight (RBW). Students completed a written survey designed by the authors; the survey gathered details of backpack wear and usage including carry time, activity level, locker use, and potentially associated back pain. Results: A majority (66.7%) of students (N = 78) reported back pain. Discriminant function analysis revealed RBW does not predict reported frequency of back pain (P = 0.96), nor did the percent of online textbooks (P = 0.23). However, a crosstab analysis showed that adolescents who carried a loaded backpack more frequently between classes reported greater frequency of back pain (P = 0.001). Conclusions: Back pain is a noted complaint amongst adolescents. The results of this study challenge the literature highlighting RBW as responsible for back pain in adolescents and asserts, instead, that longer wear time attributed to infrequent locker use for storage is responsible for back pain in this middle school sample of adolescents. Students should be encouraged to use lockers between classes to decrease carrying time of loaded backpacks.